Prevalence of overt and subclinical thyroid dysfunction among women and its effects on maternal and fetal outcome - Kumari, Puja; Singh, Sadhana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Objective of present study was to determine the current prevalence of thyroid dysfunction in normal pregnant women and to study the impact of thyroid dysfunction on maternal and fetal outcome. Methods: 400 pregnant women between 13 and 26 weeks of gestation were registered for the study. Apart from routine obstetrical investigations, TSH tests were done. Free T4 and anti-TPO antibody tests were done in patients with deranged TSH. Patients were followed up till delivery. Their obstetrical and perinatal outcomes were noted. Results: The prevalence of hypothyroidism and hyperthyroidism was and 1.25%, respectively. Adverse maternal effects in overt hypothyroidism included preeclampsia (16.6 vs. 7.8%) and placental abruption (16.6 vs. 0.8%). Subclinical hypothyroidism was associated with preeclampsia (22.3 vs. 7.8%) as compared to the euthyroid patients. Adverse fetal outcome in overt hypothyroidism included spontaneous abortion (16.6 vs. 2.39%), preterm birth (33.3 vs. 5.8%), low birth weight (50 vs. 12.11%), intrauterine growth retardation (25 vs. 4.9%), and fetal death (16.6 vs.7%) as compared to the euthyroid women. Adverse fetal outcomes in subclinical hypothyroidism included spontaneous abortion (5.5 vs. 2.39%), preterm delivery (11.2 vs. 5.8%), low birth weight (25 vs. 12.11%), and intrauterine growth retardation (8.4 vs. 4.9%) as compared to the euthyroid women. Conclusions: The prevalence of thyroid disorders was high in our study with associated adverse maternal and fetal outcomes. Routine screening of thyroid dysfunction is recommended to prevent adverse fetal and maternal outcome.